Chromium-doped strontium lithium fluoroaluminate crystal as well as growth method and application thereof

By using the mixture of sintered Cr:LiSrAlF6 crystal and ZnF2 in the lifting method for crystal growth, the problems of blank fragmentation and poor optical quality during the growth of Cr:LiSrAlF6 crystals in the prior art are solved, and higher yield and optical performance are achieved.

CN119913604AInactive Publication Date: 2025-05-02FUJIAN CASTECH CRYSTALS
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411923481.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-05-02
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When the existing Cr:LiSrAlF6 crystals are grown by lifting method, the crystal blanks are severely broken and the optical quality is poor.

Method used

By mixing CrF3, LiF, SrF2, and AlF3, sintering in an HF atmosphere, a sintered material was obtained, and then mixed with ZnF2 and then grown crystals by lifting method under a protective atmosphere.

Benefits of technology

It significantly improves the moldability and growth yield of the crystal, improves the optical properties of the crystal, and avoids cracking during growth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913604A_ABST
    Figure CN119913604A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of laser crystals, in particular to a growth method of a chromium-doped strontium lithium fluoroaluminate crystal. The growth method provided by the invention comprises the following steps: firstly, mixing CrF3, LiF, SrF2 and AlF3, and sintering in an HF atmosphere to obtain a sintered material; when the sintered material is used in the subsequent crystal growth process and is matched with ZnF2, the formability of the crystal can be obviously improved, the growth yield of the crystal is improved, and the optical performance of the prepared crystal is relatively high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of laser crystals, and in particular to a chromium-doped lithium strontium fluoroaluminate crystal and a growth method and application thereof. Background Art

[0002] Cr:LiSrAlF6 crystal is a new type of laser crystal after chrysoberyl and titanium sapphire. Its excellent performance is manifested in wide near-infrared tuning, large emission cross-section, long fluorescence lifetime, high optical damage threshold, high concentration doping without concentration quenching, small thermal lens effect, and small excited state absorption. It is often used for flash lamps and laser diode pumping.

[0003] There are several methods for growing Cr:LiSrAlF6 crystals, such as zone melting method, Czochralski method, crucible descent method, etc. Among them, the Czochralski method is more common. However, in the existing Czochralski method crystal growth, the Cr:LiSrAlF6 crystal blank is severely broken and the crystal optical quality is poor. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of severe crystal blank fragmentation and poor crystal optical quality in the existing Cr:LiSrAlF6 crystal growth using the Czochralski method, and further provide a chromium-doped lithium strontium fluoroaluminate crystal and its growth method and application.

[0005] The scheme adopted by the present invention is as follows:

[0006] The invention provides a method for growing chromium-doped lithium strontium fluoroaluminate crystals, comprising the following steps: mixing CrF3, LiF, SrF2 and AlF3 and sintering the mixture in an HF atmosphere to obtain a sintered material; mixing the sintered material and ZnF2 and growing the crystals in a protective gas atmosphere by a Czochralski method to obtain chromium-doped lithium strontium fluoroaluminate crystals.

[0007] Preferably, the chemical formula of the chromium-doped lithium strontium fluoroaluminate crystal is Cr x LqCy 1-x F6, where 0.01<x<0.05.

[0008] Preferably, the molar ratio of CrF3, LiF, SrF2, and AlF3 is (0.01-0.05): (1.03-1.07): 1: (0.95-0.99)

[0009] Preferably, the mixing process is carried out in a mixer;

[0010] Preferably, the mixing process has a rotation speed of 10-30 r / min and a mixing time of 20-40 h.

[0011] Preferably, the sintering process is carried out in a fluoriding furnace;

[0012] Preferably, the amount of HF gas introduced during the sintering process is 20-80 L / h;

[0013] Preferably, the purity of the HF is greater than or equal to 99.9%;

[0014] Preferably, the sintering process is to heat the material to 800-1100° C. at a heating rate of 5-15° C. / min, keep the temperature for 4-10 hours, and then cool the material in the furnace to obtain a sintered material.

[0015] Preferably, the mass ratio of the sintering material to ZnF2 is 100:(0.1-1).

[0016] Preferably, during the crystal growth process using the Czochralski method, the pulling speed is 5-20 rpm, the pulling speed is 0.5-4 mm / h, and the growth cycle is 40-80 h.

[0017] Optionally, during the crystal growth process by the Czochralski method, the pulling speed is 5, 10, 15 or 20 rpm.

[0018] Optionally, the selectable pulling speed is 0.5, 1, 2 or 4 mm / h.

[0019] Preferably, the crystal growth process of the Czochralski method is carried out in a protective gas atmosphere of N2 and CF4;

[0020] Wherein, the gas flow rate of N2 is 50-100 L / h; the gas flow rate of CF4 is 1-10 L / h;

[0021] Preferably, the purity of N2 is greater than or equal to 99.99%; the purity of CF4 is greater than or equal to 99.999%.

[0022] Preferably, the temperature for crystal growth by the Czochralski method is 900-1000°C;

[0023] Preferably, the diameter of the chromium-doped lithium strontium fluoroaluminate crystals obtained by the Czochralski method is 15-25 mm; the mass of the chromium-doped lithium strontium fluoroaluminate crystals obtained by the Czochralski method is 100-250 g.

[0024] Preferably, the crystal growth by the Czochralski method is performed in a graphite crucible.

[0025] Optionally, the diameter of the graphite crucible is 80-120 mm.

[0026] Optionally, the total amount of the sintering material and the ZnF2 mixed material in the crystal growth by the Czochralski method is 800-1200 g.

[0027] The present invention also provides a chromium-doped lithium strontium fluoroaluminate crystal prepared by the above-mentioned preparation method.

[0028] The present invention also provides a chromium-doped lithium strontium fluoroaluminate crystal prepared by the above-mentioned preparation method or the use of the above-mentioned chromium-doped lithium strontium fluoroaluminate crystal in a laser.

[0029] Beneficial effects of the present invention:

[0030] The invention provides a method for growing chromium-doped lithium strontium fluoroaluminate crystals, comprising the following steps: mixing CrF3, LiF, SrF2 and AlF3, and sintering the mixture in an HF atmosphere to obtain a sintered material; mixing the sintered material and ZnF2, and growing the crystals in a protective gas atmosphere by a Czochralski method to obtain chromium-doped lithium strontium fluoroaluminate crystals.

[0031] In the growth method provided by the present invention, first, CrF3, LiF, SrF2, and AlF3 are mixed and sintered in an HF atmosphere to obtain a sintered material; the sintered material is used in the subsequent crystal growth process and combined with ZnF2, which can significantly improve the formability of the crystal, improve the growth yield of the crystal, and make the optical properties of the prepared crystal higher.

[0032] Furthermore, in the growth method provided by the present invention, the pulling speed during the crystal growth process by the pulling method is 5-20 rpm, the pulling speed is 0.5-4 mm / h, and the growth period is 40-80 h;

[0033] This parameter can be matched with the raw material of the present invention, so as to avoid cracking during the growth process of the crystal and improve the yield.

[0034] Furthermore, in the growth method provided by the present invention, the crystal growth process is carried out by the Czochralski method in an atmosphere of N2 and CF4;

[0035] For the growth of chromium-doped lithium strontium fluoroaluminate crystals, the choice of atmosphere is very important. In an air atmosphere, chromium-doped lithium strontium fluoroaluminate crystals will break during the growth process. In the present application, the selection of a specific atmosphere can avoid cracking during the growth process of the crystal, and the yield is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 The sintered material after sintering in Example 1;

[0038] Figure 2The chromium-doped lithium strontium fluoroaluminate crystal obtained in Example 1;

[0039] Figure 3 The mixed material of Comparative Example 1;

[0040] Figure 4 The chromium-doped lithium strontium fluoroaluminate crystal obtained in Comparative Example 1;

[0041] Figure 5 The transmittance (350-800nm) of the chromium-doped lithium strontium fluoroaluminate crystal slice obtained in Example 1;

[0042] Figure 6 The transmittance (350-800nm) of the chromium-doped lithium strontium fluoroaluminate crystal slice obtained in Comparative Example 1;

[0043] Figure 7 is the absorption coefficient (350-800nm) of the chromium-doped lithium strontium fluoroaluminate crystal slice obtained in Example 1;

[0044] Figure 8 Absorption coefficient of the chromium-doped lithium strontium fluoroaluminate crystal slice obtained in Comparative Example 1 (350-800nm). DETAILED DESCRIPTION

[0045] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the guidance of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0046] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be purchased commercially.

[0047] Example 1

[0048] This embodiment provides a method for growing chromium-doped lithium strontium fluoroaluminate crystals, comprising the following steps:

[0049] (1) 0.093 mol CrF3, 4.64 mol SrF2, 4.55 mol AlF3 and 4.86 mol LiF were mixed in a mixer at a speed of 20 r / min for 30 h, and then put into a graphite crucible. HF gas with a purity of 99.9% was introduced into a fluorination furnace at a ventilation rate of 50 L / h. The temperature was raised to 1000°C at a heating rate of 10°C / min and kept at this temperature for 5 h. After the power was turned off and the furnace was cooled, an emerald green polycrystalline sintered material was obtained (see Figure 1 );

[0050] (2) 1000 g of the sintered material and 2 g of ZnF2 were mixed and placed in a graphite crucible with a diameter of 100 mm. The crystals were grown in a pulling furnace at a temperature of 950° C., a rotation speed of 10 rpm, a pulling speed of 2 mm / h, and a pulling time of 70 h. During the crystal growth process, 80 L / h of N2 (purity of 99.99%) and 5 L / h of CF4 gas (purity of 99.999%) were introduced. Finally, chromium-doped lithium strontium fluoroaluminate crystals with a length of 14 cm and a diameter of 25 mm (mass of about 200 g) were obtained (see Figure 2 ); its molecular formula is: Cr 0.02 LqCy 0.98 F6.

[0051] Example 2

[0052] This embodiment provides a method for growing chromium-doped lithium strontium fluoroaluminate crystals, comprising the following steps:

[0053] (1) 0.093 mol CrF3, 4.64 mol SrF2, 4.55 mol AlF3 and 4.86 mol LiF were mixed in a mixer at a speed of 20 r / min for 30 h, and then loaded into a graphite crucible. HF gas with a purity of 99.9% was introduced into a fluorination furnace at a ventilation rate of 50 L / h, and the temperature was increased to 1000°C at a heating rate of 10°C / min and kept at this temperature for 5 h. After the power was turned off and the furnace was cooled, an emerald green polycrystalline sintered material was obtained;

[0054] (2) 1000 g of sintered material and 2 g of ZnF2 were mixed and placed in a graphite crucible with a diameter of 100 mm, and crystals were grown in a pulling furnace. The crystal growth temperature was 950° C., the rotation speed during the growth process was 10 rpm, the pulling speed was 2 mm / h, and the pulling time was 70 h. During the crystal growth process, 85 L / h of N2 (purity of 99.99%) was introduced, and finally a chromium-doped lithium strontium fluoroaluminate crystal with a diameter of 25 mm was obtained. Its molecular formula is: Cr 0.02 LqCy 0.98 F6.

[0055] Example 3

[0056] This embodiment provides a method for growing chromium-doped lithium strontium fluoroaluminate crystals, comprising the following steps:

[0057] (1) 0.093 mol CrF3, 4.64 mol SrF2, 4.55 mol AlF3 and 4.86 mol LiF were mixed in a mixer at a speed of 20 r / min for 30 h, and then loaded into a graphite crucible. HF gas with a purity of 99.9% was introduced into a fluorination furnace at a ventilation rate of 50 L / h, and the temperature was increased to 1000°C at a heating rate of 10°C / min and kept at this temperature for 5 h. After the power was turned off and the furnace was cooled, an emerald green polycrystalline sintered material was obtained;

[0058] (2) 1000 g of sintered material and 2 g of ZnF2 were mixed and placed in a graphite crucible with a diameter of 100 mm, and crystals were grown in a pulling furnace. The crystal growth temperature was 950° C., the rotation speed during the growth process was 10 rpm, the pulling speed was 2 mm / h, and the pulling time was 70 h. During the crystal growth process, 85 L / h of CF4 gas (purity of 99.999%) was introduced, and finally a chromium-doped lithium strontium fluoroaluminate crystal with a diameter of 25 mm was obtained. Its molecular formula is: Cr 0.02 LqCy 0.98 F6.

[0059] Comparative Example 1

[0060] This comparative example provides a method for growing chromium-doped lithium strontium fluoroaluminate crystals, comprising the following steps:

[0061] (1) 0.093 mol CrF3, 4.64 mol SrF2, 4.55 mol AlF3 and 4.86 mol LiF were mixed in a mixer at a speed of 20 r / min for 30 h to obtain a mixture (see Figure 3 );

[0062] (2) 1000 g of the mixture and 2 g of ZnF2 were mixed and placed in a graphite crucible with a diameter of 100 mm, and crystals were grown in a pulling furnace. The crystal growth temperature was 950° C., the rotation speed during the growth process was 10 rpm, the pulling speed was 2 mm / h, and the pulling time was 70 h. During the crystal growth process, 80 L / h of N2 (purity of 99.99%) and 5 L / h of CF4 gas (purity of 99.999%) were introduced, and finally chromium-doped lithium strontium fluoroaluminate crystals with a diameter of 25 mm were obtained (see Figure 4 ); its molecular formula is: Cr 0.02 LqCy 0.98 F6.

[0063] Comparative Example 2

[0064] This comparative example provides a method for growing chromium-doped lithium strontium fluoroaluminate crystals, comprising the following steps:

[0065] (1) 0.093 mol CrF3, 4.64 mol SrF2, 4.55 mol AlF3 and 4.86 mol LiF were mixed in a mixer at a speed of 20 r / min for 30 h, and then loaded into a graphite crucible. HF gas with a purity of 99.9% was introduced into a fluorination furnace at a ventilation rate of 40 L / h, and the temperature was increased to 1000° C. at a heating rate of 10° C. / min and kept at this temperature for 5 h. After the power was turned off and the furnace was cooled, an emerald green polycrystalline sintered material was obtained;

[0066] (2) 1000 g of the sintered material was placed in a graphite crucible with a diameter of 100 mm, and the crystal was grown in a pulling furnace. The crystal growth temperature was 950° C., the rotation speed during the growth process was 10 rpm, the pulling speed was 2 mm / h, and the pulling time was 70 h. During the crystal growth process, 80 L / h of N2 (purity of 99.99%) and 5 L / h of CF4 gas (purity of 99.999%) were introduced, and finally a chromium-doped lithium strontium fluoroaluminate crystal with a diameter of 25 mm was obtained. Its molecular formula is: Cr 0.02 LqCy 0.98 F6.

[0067] Test Case

[0068] 1. Yield

[0069] The preparation methods of Examples 1, 2, 3 and Comparative Examples 1 and 2 were repeated 10 times to test the integrity of the crystals (whether they were cracked was used to determine the yield), and the yield was the number of intact crystals / 10*100% (the crystals obtained in Examples 1-3 and Comparative Examples 1-2 had a mass of about 200±15 g if intact); the test results are shown in Table 1:

[0070] Table 1

[0071] Yield Example 1 90% Example 2 60% Example 3 50% Comparative Example 1 20% Comparative Example 2 30%

[0072] 2. Transmittance test

[0073] Shimadzu spectrophotometer (UV-1700) tests the optical transmittance of the crystal cross section at 350-750nm. The test results are as follows: Figure 5 , 6 shown.

[0074] Figure 5 is the transmittance (350-800nm) of the Cr:LiSrAlF6 crystal slice grown in Example 1, Figure 6 The transmittance of the Cr:LiSrAlF6 crystal slice grown in Comparative Example 1 (350-800nm); the transmittance of the crystal prepared in Example 1 both parallel to the C-axis and perpendicular to the C-axis is much higher than the corresponding transmittance of the crystal prepared in Comparative Example 1.

[0075] 3. Absorption coefficient test

[0076] The optical weak absorption instrument PCI-02 tests the absorption coefficient of the crystal cross section in the range of 350-800nm. The test results are as follows Figure 7 , 8 shown.

[0077] Figure 7 Absorption coefficient (350-800nm) of Cr:LiSrAlF6 crystal slice grown in Example 1;

[0078] Figure 8 is the absorption coefficient (350-800nm) of the Cr:LiSrAlF6 crystal slice grown in Comparative Example 1; Figure 7 and Figure 8 It is not difficult to see that the absorption coefficient of the crystal prepared in Example 1 in the direction parallel to the C-axis and perpendicular to the C-axis is smaller than the corresponding absorption coefficient of the crystal prepared in Comparative Example 1.

[0079] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A method for growing chromium-doped lithium strontium fluoroaluminate crystals, characterized in that: The method comprises the following steps: mixing CrF3, LiF, SrF2 and AlF3 and sintering the mixture in an HF atmosphere to obtain a sintered material; mixing the sintered material and ZnF2 and growing the crystal by a Czochralski method in a protective gas atmosphere to obtain a chromium-doped lithium strontium fluoroaluminate crystal.

2. The method for growing chromium-doped lithium strontium fluoroaluminate crystals according to claim 1, characterized in that: The chemical formula of the chromium-doped lithium strontium fluoroaluminate crystal is Cr x LqCy 1-x F6, where 0.01<x<0.

05.

3. The method for growing chromium-doped lithium strontium fluoroaluminate crystals according to claim 1 or 2, characterized in that: The molar ratio of CrF3, LiF, SrF2, and AlF3 is (0.01-0.05):(1.03-1.07):1:(0.95-0.99); Preferably, the mixing process is carried out in a mixer; Preferably, the mixing process has a rotation speed of 10-30 r / min and a mixing time of 20-40 h.

4. The method for growing chromium-doped lithium strontium fluoroaluminate crystals according to any one of claims 1 to 3, characterized in that: The sintering process is carried out in a fluoriding furnace; Preferably, the amount of HF gas introduced during the sintering process is 20-80 L / h; Preferably, the purity of the HF is greater than or equal to 99.9%; Preferably, the sintering process is to heat the material to 800-1100° C. at a heating rate of 5-15° C. / min, keep the temperature for 4-10 hours, and then cool the material in the furnace to obtain a sintered material.

5. The method for growing chromium-doped lithium strontium fluoroaluminate crystals according to any one of claims 1 to 4, characterized in that: The mass ratio of the sintering material to ZnF2 is 100:(0.1-1).

6. The method for growing chromium-doped lithium strontium fluoroaluminate crystals according to any one of claims 1 to 5, characterized in that: During the crystal growth process using the Czochralski method, the pulling speed is 5-20 rpm, the pulling speed is 0.5-4 mm / h, and the growth cycle is 40-80 h.

7. The method for growing chromium-doped lithium strontium fluoroaluminate crystals according to any one of claims 1 to 6, characterized in that: The crystal growth process of the Czochralski method is carried out in a protective gas atmosphere of N2 and CF4; Wherein, the gas flow rate of N2 is 50-100 L / h; the gas flow rate of CF4 is 1-10 L / h; Preferably, the purity of N2 is greater than or equal to 99.99%; the purity of CF4 is greater than or equal to 99.999%.

8. The method for growing chromium-doped lithium strontium fluoroaluminate crystals according to any one of claims 1 to 7, characterized in that: The temperature for crystal growth by the Czochralski method is 900-1000°C; Preferably, the diameter of the chromium-doped lithium strontium fluoroaluminate crystals obtained by the Czochralski method is 15-25 mm; the mass of the chromium-doped lithium strontium fluoroaluminate crystals obtained by the Czochralski method is 100-250 g.

9. A chromium-doped lithium strontium fluoroaluminate crystal prepared by the preparation method according to any one of claims 1 to 8.

10. Use of a chromium-doped lithium strontium fluoroaluminate crystal prepared by the preparation method according to any one of claims 1 to 8 or a chromium-doped lithium strontium fluoroaluminate crystal according to claim 9 in a laser.

Citation Information

Patent Citations

  • Scintillator for neutron detection and neutron detector

    CN101945974A

  • Ultraviolet-grade calcium fluoride raw material sintering device and process

    CN111206286A

  • Raw material pre-melting furnace for crystal growth and calcium fluoride crystal raw material pre-melting method

    CN114622284A

  • Purification treatment equipment and method for calcium fluoride crystal growth raw material

    CN116676669A

  • Thorium-doped fluoride crystal and preparation method thereof, and solid nuclear light clock using thorium-doped fluoride

    CN117661114A